Fighting their own battles : Mexican Americans, African Americans, and the struggle for civil rights in Texas - Behnken, Brian D. (The University of North Carolina Press, 2011)
Behnken explores the cultural dissimilarities, geographical distance, class tensions, and organizational differences that all worked to separate blacks' and Mexican Americans' civil rights struggles in Texas.